2024
DOI: 10.1037/met0000498
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of correlation coefficients: A cautionary tale on treating measurement error.

Abstract: A scale to measure a psychological construct is subject to measurement error. When meta-analyzing correlations obtained from scale scores, many researchers recommend correcting for measurement error. I considered three caveats when correcting for measurement error in meta-analysis of correlations: (a) the distribution of true scores can be non-normal, resulting in violation of the normality assumption for raw correlations and Fisher's z transformed correlations; (b) coefficient alpha is often used as the relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(36 citation statements)
references
References 66 publications
1
30
0
Order By: Relevance
“…Another potential limitation is that the correlations in our meta‐analyses were not adjusted for the unreliability of the variables. Zhang ( 2021 ) recommended that meta‐analyses with continuous variables should correct for coefficient alpha to obtain an accurate mean effect size estimate, corrected for measurement error. However, Meta‐Essentials does not provide this functionality, adjusting effect sizes upwards can lead to unjustifiably large mean effect sizes, and not all included studies reported on the reliability of their measures Lipsey and Wilson ( 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another potential limitation is that the correlations in our meta‐analyses were not adjusted for the unreliability of the variables. Zhang ( 2021 ) recommended that meta‐analyses with continuous variables should correct for coefficient alpha to obtain an accurate mean effect size estimate, corrected for measurement error. However, Meta‐Essentials does not provide this functionality, adjusting effect sizes upwards can lead to unjustifiably large mean effect sizes, and not all included studies reported on the reliability of their measures Lipsey and Wilson ( 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pooled correlations were obtained for the total sample and separately for the clinical and non-clinical subsamples. Deviating from the preregistered protocol, it was not adjusted for score unreliability because reliability is usually reported as Cronbach's alpha, but important assumptions (e.g., tau-equivalence) for using alpha are often not met ( 38 ).…”
Section: Methodsmentioning
confidence: 99%
“…Provided accurate transformation from the mean z-transformed correlation estimates and the associated confidence intervals to the estimates and confidence intervals of (Hafdahl, 2009;Law, 1995), meta-analysis using both the raw correlations and z-transformed correlations will yield reasonably accurate estimates and inferences of . Extending from these former studies, Zhang (2022) examined these two approaches with non-normal X and Y scores and no artefacts in one of the simulations and found that they still yielded in general reasonably accurate estimates and good coverage rates for .…”
Section: Introductionmentioning
confidence: 98%
“…More relevantly, Hedges (1988) discussed the correction of both z-transformed correlation estimates and within-study sampling error variance to estimate and statistically infer . 1 In their major simulation studies, Zhang (2022) examined the performance of meta-analyses of z-transformed correlations wherein individual z-transformed correlations were corrected for measurement error using coefficient alpha based on Hedges (1988, Eq. 5) and 1∕(N i − 3) was used as the within-study sampling error variance estimate.…”
Section: Introductionmentioning
confidence: 99%